Choral works by Alexander Jacobchuk: genre and style parameters - Kushniruk, Olga (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
Relevance of study. In the context of evolution of a modern Ukrainian musical space, choir performance plays a special role. This state of affairs is based on the strong long tradition of collective singing, the extensive system of its professional and amateur functioning in modern conditions — from the titular collectives of the country to choral circles in educational institutions, church choirs in temples, and in the end it owes a large and diverse composer's heritage of past and present times. Scientific knowledge of the latter one is a necessary component in understanding the processes of development in national musical culture. In particular, despite of the active presence in the performance, creative heritage in the field of choral music of a representative of the Kyiv composer's school, the Honored Art Worker of Ukraine, the winner of the awards to them. I. Ogienko, A. Vedel, I. Nechuy-Levytskyi, the winner of the national and international composer competitions of Alexander Jacovchuk (born in 1952) continues to remain unreleased by musicologists. Main objectives of the study. To highlight the genre priorities of choral works of contemporary Ukrainian composer A. Jacovchuk and to find out some features of the author's style of the artist. The methodology of the research is based on the application of the cultural approach, source study, textual methods, as well as methods of holistic analysis and interviewing. Results and conclusions. Genre parameters of choral works by A. Jacobchuk are concentrated around the arrangement of folk songs, spiritual compositions, cantatas, poems, lesser oratorios, mini cycles, mixed genre of symphony oratorios. Among the stylistic features of the author`s manner in choral music — modality as the basis of mode thinking, vibrant polyphonic technique, drama of choral timbres, tactful application of intertextuality and stylization, originality of compositional solution (reduction of reprise), derived from reading the word concentration of musical intonation and its main influence on the entire intonational field of the work. In the future for next investigation of the artist`s works an important separate step is to find out the genre-style features of his large-scale compositions — the oratorios "Scythian Pectoral", "Passion for Christ."